INDEX - Canadian Association for Information Science; Amand, Havelin; Anderson, S.; Brennan, M-L.; Deschatelets, Gilles H.; Drover, Ellis R.; Grande, Sally; Heseltine, Inez; Howard, Helen; MacKinnon, R.; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF